2018
DOI: 10.3802/jgo.2018.29.e62
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between adjuvant chemotherapy and adjuvant radiotherapy/chemoradiotherapy after radical surgery in patients with cervical cancer: a meta-analysis

Abstract: ObjectiveTo estimate the effect of adjuvant chemotherapy (AC) on the prognosis in cervical cancer patients with intermediate- or high-risk factors after radical hysterectomy (RH) compared to that for adjuvant radiotherapy (AR).MethodsThe Embase and MEDLINE databases and the Cochrane Library were searched for published studies comparing cervical cancer patients who received AC with those who received AR after RH. The endpoints were patient oncologic outcome. Random-effects meta-analytical models were used to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…However, the results of this analysis are encouraging, showing that the rates of recurrence were comparably lower than the LACC results and with adjuvant treatment in the vast majority with chemotherapy only, without additional radiotherapy; thus, locoregional tumor control could be attributed to surgery alone with low morbidity. A meta‐analysis showed that compared to adjuvant radiotherapy, adjuvant chemotherapy showed similar survival outcomes in cervical cancer patients undergoing radical hysterectomy and also appeared to reduce the risk of distant recurrence . The third is that because MIRH for early‐stage cervical cancer has been proactively performed in our hospital as first‐line therapy since 2000, the subjects included very few cases of open surgery, rendering the presentation of comparative data for MIRH and ORH not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of this analysis are encouraging, showing that the rates of recurrence were comparably lower than the LACC results and with adjuvant treatment in the vast majority with chemotherapy only, without additional radiotherapy; thus, locoregional tumor control could be attributed to surgery alone with low morbidity. A meta‐analysis showed that compared to adjuvant radiotherapy, adjuvant chemotherapy showed similar survival outcomes in cervical cancer patients undergoing radical hysterectomy and also appeared to reduce the risk of distant recurrence . The third is that because MIRH for early‐stage cervical cancer has been proactively performed in our hospital as first‐line therapy since 2000, the subjects included very few cases of open surgery, rendering the presentation of comparative data for MIRH and ORH not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The survival outcome of patients with cervical cancer receiving adjuvant chemotherapy and/ or adjuvant radiotherapy (chemoradiotherapy) after radical hysterectomy are similar, and the risk of distant recurrence is reduced. 1 Neoadjuvant chemotherapy followed by radical surgery also has a favorable prognosis for locally advanced cervical cancer. 2,3 The main chemotherapy regimens for this disease include platinum-based drugs and taxanes.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the most common malignant tumors in the world for woman. Adjuvant chemotherapy and adjuvant radiotherapy (chemoradiotherapy) after radical hysterectomy show similar survival outcomes in cervical cancer patients and also appear to reduce the risk of distant recurrence (1). Neoadjuvant chemotherapy followed by radical surgery also predicts a favorable prognosis for local advanced cervical cancer (2,3).…”
Section: Introductionmentioning
confidence: 99%